OGC P24 The effect of the pandemic on the number of examined lymph nodes following major oesophophagogastric resection. (7th December 2022) - Youssef, Fady; Jackson, Andrew; Hossain, Tanvir; Trotter, Martin; Yanni, Fady; Parsons, Simon L
Abstract: Background: Lymph node yield following oesophagogastric (OG) cancer resection remains a valuable prognosticator of overall patient survival. It is also a quality indicator of histopathological assessment and a surrogate marker of surgical technique. The Royal College of Pathologists' state a minimum lymph node yield of 15 per specimen should obtained in 100% of cases where a radical OG resection has been undertaken. It is well known that the COVID-19 pandemic placed immense strain on NHS services. This study aimed to evaluate its effect on lymph node yield reporting following major OG resection in a large volume tertiary unit. Methods: Retrospective National OG Cancer Audit (NOGCA) metrics were collected. Histological data including total lymph node yield and positive node status were extracted from patient records. Patient data was categorised into two study periods; pre-pandemic (March 2018-Feb 2020) and pandemic (March 2020- Feb 2022) following the first UK national lockdown. Comparative analysis between the two study periods was performed and for lymph node yield >15 per specimen a X 2 statistic calculated. Results: In the pre COVID period a total of 280 (excluding GIST) resections were performed, 75% (210) oesophagectomies v. 25% (70) gastrectomies. The median age was 69 (range 25–90, males= 189 v. females =91). In the post pandemic period a total of 188 resections were performed, 72% (135) oesophagectomies v. 28% (53) gastrectomies. The median age was 69 (38–87, males = 142 v. female= 46). Lymph node yield was available for 275 resections in pre-pandemic study period, with a median nodal yield of 20 (5–61). In the pandemic study period lymph node yield data was available for 180 patients, median 19.5 (0–69). The minimum nodal yield (>15) was obtained in 80.7% of resection specimens pre-pandemic v. 68.9% in the pandemic study period (p= 0.00382). Conclusions: Our study demonstrates a higher rate of inadequate nodes examined in the post pandemic study period. Despite staffing pressures, efforts should be made to improve number of nodes examined to provide robust prognostic data.